A kinematic comparison of on-ergometer and on-water kayaking. Issue 10 (3rd October 2021) - Klitgaard, Kent K.; Hauge, Christian; Oliveira, Anderson Souza; Heinen, Frederik
Abstract: The aim of this study was to compare the kinematic profile of on-water and on-ergometer kayaking during maximal paddling. Eleven elite junior female kayak athletes (Mean SD, age: 16.8 ± 1.2 years; body mass: 64.1 ± 8.1 kg) performed a 2-minute maximal kayaking exercise with their competition equipment on water, and a 2-minute maximal kayaking exercise on a standard ergometer. Kinematic data was recorded with an inertial motion capture system. Elbow, shoulder and knee angles and their respective angular velocities were extracted and normalised with respect to the stroke cycle. Statistical Parametric Mapping (SPM) was used to identify statistically significant differences between the two conditions. The stroke rate was significantly higher on ergometer (122.1 ± 6.8 strokes per minute) compared to on water (107.1 ± 4.6 strokes per minute, p  < 0.05), with a difference of 8.4 ± 5.9 strokes per minute. Elite kayak female athletes exhibited differences in elbow, shoulder and knee kinematics when comparing on-ergometer to on-water performance. Moreover, the results demonstrated an increased range of motion in lateral bending in the thoracolumbar joint ( p  < 0.001). The current results support recent findings that a kayak ergometer may not replicate on-water kinematics.